Electronic Word of Mouth (E-WOM) factor in social media that influence purchase intention in online business / Farah Syuhadah Fuad - Fuad, Farah Syuhadah (2017)
Electronic Word of Mouth (WOM) has been used for centuries to spread words about a product or services by the customer which is way before medium such as social networking site are created. However, by the existence of social networking site WOM are taken to another level and known as Electronic Word of Mouth (EWOM). Through EWOM information and review about a product or services are able to reach much more audience compare to WOM this is important for firm as EWOM might increase customer purchase intention. This study attempt to find factors of EWOM which is SNS involvement, quality, credibility, attitude toward information) that influence the purchase intention of customer in online shopping. Data for the study were collected through self-administered survey and online survey using Google docs. SPSS Statistics 20 are used to analyse the data. This study finds that EWOM credibility and attitude toward information has a relationship with purchase intention however, SNS involvement and EWOM quality does not have a association with purchase intention. The result of this study are important for business to strategies their marketing strategy in the online setting to raise the consumer purchase intention.